2020
DOI: 10.3390/su12229771
|View full text |Cite
|
Sign up to set email alerts
|

On the Settlement of the Floating Population in the Pearl River Delta: Understanding the Factors of Permanent Settlement Intention versus Housing Purchase Actions

Abstract: Previous investigations of the settlement intentions of China’s floating population have been undermined by an oversimplification of the concepts and measurements related to settlement intentions. More attention should be paid to influencing factors from the theoretical framework of “place utility” in new periods. Based on this framework, we use a multinormal logistic regression model to explore the impact of economic, human capital, and social factors on migration intentions and housing purchase actions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Previous studies have demonstrated that the settlement intention is shaped by a series of socioeconomic factors [ 4 , 16 , 46 , 51 , 52 , 53 , 54 ], including household factors (e.g., family members, housing type, and household income per capita), occupational status (e.g., employed sectors, job duration, and monthly wage), and social factors (e.g., physical health, relationship with local residents, and migration experience). However, individual samples taken in this database did not contain these variables and therefore could not be taken into account for the effects of socioeconomic factors on floating populations’ actual urban settlement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the settlement intention is shaped by a series of socioeconomic factors [ 4 , 16 , 46 , 51 , 52 , 53 , 54 ], including household factors (e.g., family members, housing type, and household income per capita), occupational status (e.g., employed sectors, job duration, and monthly wage), and social factors (e.g., physical health, relationship with local residents, and migration experience). However, individual samples taken in this database did not contain these variables and therefore could not be taken into account for the effects of socioeconomic factors on floating populations’ actual urban settlement.…”
Section: Discussionmentioning
confidence: 99%
“…Less attention has been paid to the role of housing types in integration. Housing provides housing security, public services, and upward mobility opportunities (such as school provisions organized around the catchment areas) for the migrants [ 31 ]. In China, hukou imposes limits on the social integration of migrants, but recent studies have indicated that the migrants tend to achieve permanent settlement through more flexible channels such as purchasing urban housing in the destination city, even though the migrants have limited housing opportunities than residents since that house prices are particularly high in big cities [ 32 , 33 ].…”
Section: Social Integration Of Aging Migrants In China: Review and Co...mentioning
confidence: 99%
“…In other countries, the typical migration process is that migrants permanently settle in a city after they have lived and worked there for some time. [30,31]. In China, however, many migrants are part of the floating population, residing in a certain location for a time before moving to the next, without ever settling.…”
Section: Economic Cultural and Institution Factors Influencing Settlement Intentionmentioning
confidence: 99%
“…Educational attainment is a critical reflection of human capital. More highly educated people face fewer challenges in economic and social integration in city life [31,52]. Specifically, educational attainment was crucial for the present rural-urban migrants, whose educational attainment was low overall.…”
Section: Factors Influencing Settlement Intention In All Migrantsmentioning
confidence: 99%